NEW RECORD SPECIES OF GIANT FRESH WATER SHRIMP FROM THE DOWNSTREAM OF SERAYU RIVER - Baruna K.; S. B. Prayitno; A. Sabdaningsih; P. H. T. Soedibya; S. W. Saputra (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Indonesia is characterized by great diversity of freshwater shrimp, consisting of several islands due to the geographical location on the equator. A recent investigation conducted in Central Java has identified Serayu River as the major habitat of freshwater shrimp genus Macrobrachium. Therefore, this research aimed to determine the type of giant freshwater shrimp found downstream of Serayu River using explanatory method. The experiment was conducted for one year (January - December 2023) and the results found two freshwater giant prawn species, namely Macrobrachium rosenbergii and Macrobrachium spinipes. Moreover, this research is the first record of M. spinipes based on the Cytochrome C oxidase Subunit I (CO1) gene. The mtDNA segment of M. rosenbergii was 631 bp (base pairs) (GenBank accession: LC813231.1), while M. spinipes was 616 bp (GenBank accession: PP735157.1). M. spinipes and M. rosenbergii downstream of Serayu River showed similar locations and characteristics. Genetic distance conducted on 15 species of the genus Macrobrachium showed that giant freshwater prawn serayu had a matrix value of 0.09 - 0.18. Genetic analysis conducted with GenBank indicated that M. spinipes showed significant differences from other species, suggesting the natural dispersal of juvenile through currents across Wallace Line. This research also found that M. rosenbergii was similar to M. dacqueti and related to M. malcolmsonii, while M. spinipes was close to M. suphanense. To support these results, recommendation was made to explore further the rivers in the western part of Java, Indonesia.